Deposit Insurance and Financial Development - Cull, Robert; Senbet, Lemma W.; Sorge, Marco (World Bank, Washington, DC, 2014)
The authors examine the effect of different design features of deposit insurance, on long-run financial development, defined to include the level of financial activity, the stability of the banking sector, and the quality of resource allocation. Their empirical analysis is guided by recent theories of banking regulation, that employ an agency framework. The authors examine the effect of deposit insurance on the size, and volatility of the financial sector, in a sample of fifty eight countries. They find that generous deposit insurance, leads to financial instability in lax regulatory environments. But in sound regulatory environments, deposit insurance does have the desired impact on financial development, and growth. Thus, countries introducing a deposit insurance scheme, need to ensure that it is accompanied by a sound regulatory framework. Otherwise, the scheme will likely lead to instability, and deter financial development. In weak regulatory environments, policymakers should at least limit deposit insurance coverage.